Impact of forest harvesting on trophic structure of eastern Canadian Boreal Shield lakes: insights from stable isotope analyses. - Patricia Glaz; Pascal Sirois; Philippe Archambault; Christian Nozais (PLoS ONE)
Perturbations on ecosystems can have profound immediate effects and can, accordingly, greatly alter the natural community. Land-use such as forestry activities in the Canadian Boreal region have increased in the last decades, raising concerns about their potential impact on aquatic ecosystems. The objective of this study was to evaluate the impact of forest harvesting on trophic structure in eastern Canadian Boreal Shield lakes. We measured carbon and nitrogen stable isotopes values for aquatic primary producers, terrestrial detritus, benthic macroinvertebrates, zooplankton and brook trout (Salvelinus fontinalis) over a three-year period in eight eastern Boreal Shield lakes. Four lakes were studied before, one and two years after forest harvesting (perturbed lakes) and compared with four undisturbed reference lakes (unperturbed lakes) sampled at the same time. Stable isotope mixing models showed leaf-litter to be the main food source for benthic primary consumers in both perturbed and unperturbed lakes, suggesting no logging impact on allochthonous subsidies to the littoral food web. Brook trout derived their food mainly from benthic predatory macroinvertebrates in unperturbed lakes. However, in perturbed lakes one year after harvesting, zooplankton appeared to be the main contributor to brook trout diet. This change in brook trout diet was mitigated two years after harvesting. Size-related diet shift were also observed for brook trout, indicating a diet shift related to size. Our study suggests that carbon from terrestrial habitat may be a significant contribution to the food web of oligotrophic Canadian Boreal Shield lakes. Forest harvesting did not have an impact on the diet of benthic primary consumers. On the other hand, brook trout diet composition was affected by logging with greater zooplankton contribution in perturbed lakes, possibly induced by darker-colored environment in these lakes one year after logging.